Successful recanalisation of coronary chronic total occlusions is not associated with improved cardiovascular survival compared with initial medical therapy. (2nd November 2019) - Guo, Lei; Zhang, Shanfeng; Wu, Jian; Zhong, Lei; Ding, Huaiyu; Xu, Jiaying; Zhou, Xuchen; Huang, Rongchong
Abstract: Objective. To compare the clinical outcomes associated with successful percutaneous coronary intervention (PCI) versus initial medical therapy (MT) in patients with coronary chronic total occlusions (CTOs). Methods. Between January 2007 and December 2016, a total of 1702 patients with ≥1 CTO were enrolled. Patients who had a failed CTO-PCI were excluded. After exclusion, 1294 patients with 1520 CTOs were divided into the MT group initially (did not undergo a CTO-PCI attempt) ( n = 800) and successful PCI group ( n = 494). Propensity-score matching was also performed to adjust for baseline characteristics. The primary outcome was cardiac death. Results. The median overall follow-up duration was 3.6 (IQR, 2.1–5.0) years, there was no significant difference between the two groups with respect to the prevalence of cardiac death (MT vs. successful PCI: 6.6 vs. 3.8%, adjusted hazard ratio [HR] 0.93, 95% confidence interval [CI] 0.41–2.14, p = .867). In the propensity-matched population (286 pairs), there were no significant differences in the prevalence of cardiac death (MT vs. successful PCI: 5.9% vs. 3.1%, HR 0.51, 95% CI 0.23–1.15, p = .104) and major adverse cardiovascular events (MACE) (HR 0.76, 95% CI 0.53–1.09, p = .130) between the two groups. Conclusion. In the treatment of patients with CTOs, successful PCI is not associated with improved long-term cardiovascular survival or reduced the risk of MACE compared with MT alone initially.